Semeando e cultivando a agroecologia na metrópole de Belo Horizonte: agriculturas do Baixo Onça - Victor Gabriel de Souza Lima Alencar (2022)
The research focuses on the different agriculture experiences and practices located in Belo Horizonte, especially the agricultures of the Baixo Onça (sub-basin of the Ribeirão Onça watershed, located in the northeast and north regions of the municipality). They have shown the richness of different subjects, knowledge, forms of social organization, and spaces, as well as their capacity to supply quality food, among other elements explored. More specifically, they have shown the role that urban agriculture and agroecology can play in a metropolis, especially in the urban peripheries, which tension the different dichotomies created between city and nature. Even if agricultures present several benefits for cities and their inhabitants, they still occupy a place of invisibility and face different and combined processes of inequality. Thus, the objective of the research is to reflect and analyze the different ways and perspectives that the agricultures of the Baixo Onça indicates for the production of the metropolitan space, in which social, environmental, and economic inequality are mixed and associated, but also faced. Besides understanding the benefits and perspectives, an important part was to analyze and reflect on how much agriculture contributes to the social reproduction of these people, as well as its representativeness and centrality in their everyday lives. Thus, based on a qualitative research methodology, this dissertation presents which paths the experiences are taking and how they are articulating themselves, as well as which conflicts, contradictions and concrete possibilities point to the construction and/or permanence of spatial practices based on agroecology principles in urban contexts. It also provokes a re-evaluation of the conceptions that have been created around the urban peripheries, as a subordinate place in relation to other spaces in the city.